Análisis jurídico y doctrinario del derecho de protección especial de las mujeres embarazadas en el ámbito laboral. Sentencia No. 593-15-EP/21 - Luna Cuenca, Briggithe de los Ángeles (2023)
The present work entitled "Legal and doctrinal analysis of the right to special protection of pregnant women in the labor sphere. Judgment No. 593-15-EP/21" arises from the interest to investigate since it has been evidenced the violation of this right in public servants who work under occasional service contracts, provisional appointments and appointments of free removal, which violates their right to work and their rights that by their pregnancy condition correspond to them, such as: maternity leave, leave for the care and breastfeeding of the newborn, right to enhanced job stability, right to equality and non-discrimination, and respect for the reproductive rights of all working people. In addition, the dismissal of a pregnant or breastfeeding employee violates other fundamental rights such as the right to social security, health, food and in general to have a dignified life, since the lack of income does not allow the mother and the child to achieve any of these fundamental rights, For this reason, it is important that the fundamental right to special protection for pregnant or breastfeeding women be guaranteed under equal conditions, regardless of the type of appointment in which they are providing their services. In this research, materials and methods were applied that allowed the development of the investigation, as well as interviews and surveys to legal professionals whose results served to contrast the objectives and propose a possible solution to the problem posed.